2015
DOI: 10.1016/j.ijdevneu.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The responses of hypothalamic NPY and OBRb mRNA expression to food deprivation develop during the neonatal‐prepubertal period and exhibit gender differences in rats

Abstract: Neuropeptide Y (NPY) is an important hypothalamic orexigenic neuropeptide that acts in the brain. It has been established that the fasting-induced up-regulation of NPY expression is mainly caused by a reduction in the activity of leptin, which is a hormone secreted by adipose tissue. We have reported that in female rats hypothalamic NPY mRNA expression does not respond to fasting during the early neonatal period, but subsequently becomes sensitive to it later in the neonatal period. In this study, we compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…In addition, although the response of pp‐orexin (Hcrt) mRNA expression to maternal deprivation in the neonatal period has been evaluated in one study (Yamamoto et al, 2000), the response of pp‐orexin/Hcrt mRNA expression to fasting during the prepubertal period and the responses of OX1R and OX2R mRNA expression to fasting have not been examined. We have reported that the developmental patterns of some hypothalamic factors differ slightly between the sexes (Matsuzaki et al, 2015a,b). In addition, it has been reported that some neuronal factors have low sensitivities to undernutrition in prenatal and/or early neonatal period and that nutritional conditions in such period give long‐lasting effects on the development and functions of these factors (Delahaye et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although the response of pp‐orexin (Hcrt) mRNA expression to maternal deprivation in the neonatal period has been evaluated in one study (Yamamoto et al, 2000), the response of pp‐orexin/Hcrt mRNA expression to fasting during the prepubertal period and the responses of OX1R and OX2R mRNA expression to fasting have not been examined. We have reported that the developmental patterns of some hypothalamic factors differ slightly between the sexes (Matsuzaki et al, 2015a,b). In addition, it has been reported that some neuronal factors have low sensitivities to undernutrition in prenatal and/or early neonatal period and that nutritional conditions in such period give long‐lasting effects on the development and functions of these factors (Delahaye et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although we could not clarify the mechanism by which ERα and POMC mRNA expression levels are maintained in females, some unidentified factors might be involved in the discrepancies between the responses seen in each sex. In addition, we evaluated the effects of fasting on serum leptin levels using similar experimental models in a previous rat study [6]. As a result, we found that although the serum leptin levels of both sexes were reduced by 24 h fasting at all examined ages (postnatal days 10, 20, and 30), no differences between the serum leptin levels of males and females were detected under the fed or fasting conditions.…”
Section: Discussionmentioning
confidence: 86%
“…We previously found that the basal levels of central and peripheral metabolic and nutritional regulatory factors change, and their responses to metabolic status develop, during the neonatal to pre-pubertal period [5,6]. Interestingly, the developmental changes in the expression levels of some factors and their responses to a negative energy status differ between males and females [5,6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The house-keeping gene Tbp (TATA binding protein) was amplified to standardize the amount of sample RNA. Relative quantification of gene expression was achieved using the ΔCT method as described [34].…”
Section: Quantification Of Mrna Expressionmentioning
confidence: 99%